حجاجية النادرة في "ماء النخالة" للجاحظ - منصور, آمال (قــــــراءات; No 09 (2016): مجلة قراءات, 2019)
تتأسس هذه الدراسة على بيان مقومات الخطاب الحجاجي في نادرة من نوادر الجاحظ  هي "ماء النخالة" في كتابه ذائع الصيت "البخلاء"، صحيح أن فكرة الدراسة ليست جديدة من حيث الموضوع، لكنها مختلفة من حيث المعالجة، وعليه تتوزع الدراسة على قسمين مهمين: الاوّل: تفكيك الأفعال المباشرة في خطاب النادرة. أما الثاني: بيان مراحل التفاعل الحواري في نص النادرة. وأخيرا: تمثيل عناصر الجهاز الحجاجي و أساليبه في نص النادرة.هي محاولة بسيطة لولوج الخطاب العربي القديم من منظور جديد. This study is based on the description of the components of the argumentative speech in one of Al Djahid’s anecdotes which is “The Bran’s Water” in his famous book “The Misers”. It’s true that the theme of this study is not new, but different in its treatment. Thus, the study is divided into two important parts: Part one: the dissociation of the direct acts into the anecdote’s speech. Part two: the description of the dialogic interaction in the text of the anecdote.    Finally, the assimilation of the elements of the argumentative speech and of its styles in the text of the anecdote is a simple essay to accede to the ancient Arab speech in a new perspective